Применение компьютерной томографии при планировании повторного эндодонтического лечения (Эндодонтия Today, 2020)
Modern practitioners involved in endodontics have the technical capability to save the tooth. However, the anatomy of teeth may differ significantly from traditional views. The paper analyzes the theoretical and practical studies of radiological diagnostic techniques: panoramic X-Ray and computer tomography (CT), which revealed the advantages of CT over conventional radiological methods. The use of CT maximizes accurately make a diagnosis based assessment of the state of tissues and structures adjacent to the tooth. A doctor may decide to appropriate endodontic intervention, both primary and recurring.